Antirust paint for high-temperature transmission mesh belt, and preparation method and application thereof
By using an anti-rust paint formula composed of environmentally friendly nitrate ionic liquid, chitosan polymer and sunflower oil-based mixture, the shortcomings of existing anti-rust paints in terms of environmental protection and high-temperature anti-rust effect are solved, and high efficiency and environmental protection are achieved anti-corrosion protection effect of metal materials.
Patent Information
- Application Number
- CN202411966266.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing anti-rust paint has shortcomings in environmental protection and high-temperature anti-rust effect, and it is difficult to meet the demand of high-temperature transmission networks for high-performance anti-rust solutions.
The anti-rust paint formula consisting of environmentally friendly nitrate ionic liquid, chitosan polymer and sunflower oil-based mixture is used to form a stable and efficient anti-corrosion protective layer through the unique chemical structure and adsorption mechanism of these components.
It has achieved significant improvement in the corrosion resistance of metal materials under high temperature environments, reduced its impact on the ecological environment, and the formula is environmentally friendly and sustainable.
Smart Images

Figure CN119463558A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-rust paint, and in particular to anti-rust paint for high-temperature transmission mesh belts, a preparation method and applications. Background Art
[0002] With the accelerated advancement of industrialization and urbanization, high-temperature transmission networks have become a critical infrastructure supporting the operation of modern society. They serve a wide range of industries, including power plants, petrochemicals, and steel manufacturing, and are responsible for the efficient transmission of media such as heat, steam, and high-temperature hot water. However, the operating environment under these extreme working conditions, especially the strong corrosive and oxidizing properties associated with high temperatures, poses a severe challenge to the durability of transmission pipelines and equipment. They are very likely to cause rust problems, which in turn lead to frequent equipment failures, reduced energy efficiency, and even increased potential safety risks. To meet this challenge, researchers are committed to developing anti-rust paint specifically for high-temperature transmission networks. This anti-rust paint integrates a unique formula that integrates high-temperature resistance, anti-oxidation, and strong corrosion resistance. It is designed to form a strong and long-lasting protective film on the surface of pipelines and equipment through spraying, immersion, or direct injection into the internal circulation system of the pipeline, effectively isolating the corrosive medium and curbing the occurrence of rust at the source.
[0003] Despite significant progress in anti-rust paint technology, existing solutions still have limitations. A primary issue is environmental sustainability. Some anti-rust paint formulas contain ingredients such as phosphates or nitrites. The former can easily cause eutrophication of water bodies, while the latter can, under certain conditions, transform into carcinogens, posing a threat to the ecological environment and human health. Consequently, countries around the world have implemented strict regulations on the use and discharge of such anti-rust paints. For example, the technology disclosed in Chinese patent application publication number CN109135523A, while innovative, faces environmental scrutiny due to the presence of nitrites. Another major challenge is the limited effectiveness of rust prevention in high-temperature environments. Existing anti-rust coatings are typically applied at room temperature, making them difficult to fully and durably protect pipeline and equipment surfaces and ineffective against corrosion at high temperatures. Therefore, there is an urgent need to develop a new anti-rust paint that combines environmental protection with high-efficiency anti-rust performance to overcome the bottlenecks of existing technologies and meet the urgent need for high-performance anti-rust solutions in high-temperature transmission networks. This innovative effort will not only promote the advancement of industrial anti-corrosion technology but also contribute significantly to sustainable development. Summary of the Invention
[0004] (1) Technical problems solved
[0005] The purpose of the present invention is to provide a high-temperature transmission mesh belt anti-rust paint, a preparation method and an application thereof, so as to solve the problems of insufficient environmental protection and insufficient high-temperature rust resistance of current anti-rust paints.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The high-temperature transmission mesh belt anti-rust paint is made of the following components in parts by weight: 10-25 parts of environmentally friendly nitrate ion liquid, 8-24 parts of chitosan polymer, 12-24 parts of sunflower oil-based mixed liquid, 2-6 parts of sorbitol, 15-30 parts of triethanolamine, and 4-9 parts of sodium carbonate;
[0009] The preparation method of the environmentally friendly nitrate ionic liquid comprises the following steps: adding 10 to 20 parts by weight of L-proline and 25 ml of deionized water into a flask, then adding 2.5 to 5 parts of 3 mol / L nitric acid, then heating the mixture to 50 to 70° C., stirring and keeping the temperature for 20 to 40 hours, and finally vacuum drying the mixture at 50 to 60° C. for 30 to 60 minutes to obtain the environmentally friendly nitrate ionic liquid;
[0010] The preparation method of the chitosan polymer is as follows: in parts by weight, 2 to 6 parts of chitosan salt, 1 to 3 parts of lauric acid, 90 to 100 ml of deionized water and 80 to 90 ml of methanol are uniformly mixed, and then 1.5 to 3.5 parts of N, N'-dicyclohexylcarboximide are added, and the mixture is stirred for 20 to 35 hours under a nitrogen atmosphere, and then 300 parts of acetone are added for precipitation and then filtered, and then the filtered product is washed three times with methanol, each washing requires that the filtered product is completely submerged with methanol, and finally the washed filtered product is vacuum dried at room temperature.
[0011] The preparation method of the sunflower oil-based mixed liquid is as follows: 200-250 parts by weight of sunflower oil and 30-45 parts of formic acid are added to a reaction container, the temperature is then raised to 50-60° C., 100-140 parts of hydrogen peroxide are added and the reaction is continued for 3-6 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and dissolved in 300 parts of dichloromethane. Then, 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are added, the mixture is stirred evenly, and then filtered. The filtrate is then dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil. Finally, 100-140 parts of epoxy sunflower oil and 50-90 parts of polyethylene glycol 400 are mixed, and the mixture is heated to 60-80° C. and kept warm for 3 hours to carry out a ring-opening reaction to synthesize the sunflower oil-based mixed liquid.
[0012] Furthermore, the mass ratio of the L-proline to 3 mol / L nitric acid is 4:1.
[0013] The environmentally friendly nitrate ionic liquid designed in this invention serves multiple purposes: 1. From an environmental perspective, L-proline and the anions in nitric acid together form a non-toxic, environmentally friendly ionic liquid system. This design eliminates the harmful chemicals that may be used in traditional rust prevention treatments, achieving a green process from source to application, contributing to environmental protection. By adopting this green and environmentally friendly ionic liquid, the impact on the ecological environment can be effectively reduced, promoting sustainable development. 2. From a high-temperature rust prevention perspective, the accelerated adsorption of nitrate ion molecules and the increased coverage of active sites on the metal surface at high temperatures delay the corrosion cycle. The improved performance at higher temperatures may be due to the shift in adsorption mode from primarily physical to chemical properties as the temperature increases. During the chemical adsorption process, the environmentally friendly nitrate forms an iron ion complex with the metal surface. The chemical interaction formed by this iron ion complex makes it difficult for the inhibitor molecules to desorb. Secondly, the inhibitor molecules will more frequently contact the electrode surface and be adsorbed through chemical adsorption. In addition, the increase in electrolyte temperature may lead to increased desorption of water molecules from the metal surface, thereby increasing the likelihood of surface adsorption of nitrate ion molecules. Finally, the environmentally friendly nitrate ionic liquid increases the hydrophobicity of the metal surface, which further reduces the degree of metal corrosion at high temperatures. In summary, the environmentally friendly nitrate ionic liquid of the present invention not only reflects a deep concern for environmental protection, but also demonstrates excellent rust prevention effects in high-temperature environments.
[0014] Furthermore, the preparation method of the chitosan salt is as follows: in parts by weight, 3 to 7 parts of p-toluenesulfonic acid, 2 to 6 parts of chitosan and 85 parts of deionized water are mixed evenly in an argon atmosphere, and then heated and stirred at 60 to 80° C. for 20 to 30 hours. After the reaction is completed, the mixture is washed three times with ether at room temperature, and each washing requires that the reaction product be completely submerged with ether, and then dried completely in a vacuum drying oven at 34 to 45° C.
[0015] Furthermore, the mass ratio of the chitosan salt to lauric acid is 2:1.
[0016] The chitosan polymers designed in this invention serve multiple purposes: 1. From an environmental perspective, both are natural or bio-based compounds. Lauric acid is often derived from plant oils, while chitosan is produced by deacetylation of chitin. These compounds are renewable and biodegradable, reducing reliance on fossil resources and environmental pollution. 2. When used as corrosion inhibitors, these polymers effectively reduce negative impacts on the environment and ecosystems because they produce no toxic or harmful byproducts during use and are naturally degraded after use, preventing long-term accumulation in the environment. 3. From a corrosion resistance perspective, chitosan polymers exhibit excellent corrosion resistance under high-temperature conditions. 4. Chitosan's natural or bio-based origins provide it with excellent thermal stability, making it less susceptible to degradation or denaturation at high temperatures, ensuring a sustained corrosion protection effect. 5. Chitosan polymers, through their strong adsorption, adhere more tightly to metal surfaces at high temperatures, forming a dense and stable inhibitory adsorption layer. This adsorption layer effectively isolates the metal from direct contact with the corrosive medium and resists thermal stress shock in high-temperature environments, preventing the coating from cracking or shedding due to temperature fluctuations. Furthermore, chitosan polymer maintains its properties as an effective electron-donating inhibitor even at high temperatures. Due to its low energy gap, it efficiently donates electrons, forming a strong chemical bond with the metal surface at high temperatures. This strengthened chemical bond not only enhances the heat resistance of the inhibitory adsorption layer but also effectively inhibits corrosion reactions even under extreme temperatures. In summary, the anti-corrosion mechanism of chitosan polymer at high temperatures is primarily reflected in its excellent thermal stability, enhanced adsorption capacity, and its properties as an efficient electron-donating inhibitor. These mechanisms work together to enable chitosan polymer to provide reliable corrosion protection for metals under high-temperature conditions.
[0017] The sunflower oil-based mixed liquid designed by the present invention has the following multiple purposes: 1. From the perspective of environmental protection, first of all, it realizes a green alternative to traditional anti-rust paint materials. Traditional anti-rust paints often contain heavy metal ions or volatile organic compounds that are harmful to the environment. These components may cause pollution to the environment during use, and there is also great environmental pressure when disposing of discarded anti-rust paints. The sunflower oil-based mixed liquid makes full use of sunflower seed oil, a renewable and biodegradable vegetable oil resource. Its raw material source is wide and highly renewable, which is in line with the concept of sustainable development. 2. From the perspective of high-temperature rust prevention, it depends on the stable chemical adsorption layer formed by its molecules on the metal surface. Under high temperature conditions, the functional groups (such as ether groups and triglyceride groups) in the molecules of the sunflower oil-based mixed liquid interact strongly with the metal surface, and are firmly adsorbed on the metal surface through chemical bonding to form a dense protective film. This protective film can not only effectively isolate the corrosive medium from direct contact with the metal substrate, but also maintain its structural integrity and stability in a high-temperature environment, thereby significantly inhibiting the corrosion process of the metal. Furthermore, the strong interaction between the sunflower oil-based mixture molecules and the metal surface enhances the adhesion and erosion resistance of the adsorption layer, ensuring effective corrosion protection even under harsh conditions such as high-temperature fluid erosion. In summary, the sunflower oil-based mixture achieves highly effective corrosion protection for metal materials through its unique chemical adsorption mechanism and high-temperature stability.
[0018] In the present invention, sorbitol acts as a stabilizer and humectant, helping to adjust the viscosity of the anti-rust paint and maintain its stability; triethanolamine may act as an emulsifier, neutralizer or solvent, and has an important influence on the performance of the anti-rust paint; and sodium carbonate is used to adjust the pH value of the anti-rust paint to ensure that it works within an appropriate range.
[0019] The present invention also provides a method for preparing a high-temperature transmission mesh belt anti-rust paint, which comprises the following steps:
[0020] First, environmentally friendly nitrate ion liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol are added to a three-necked flask reactor, slowly heated to 50-80°C under magnetic stirring, and then stirred for 2-4 hours. During the stirring process, sodium carbonate is used to adjust the pH to 7.0-9.0, and then the high-temperature transmission mesh belt anti-rust paint is obtained after cooling.
[0021] The present invention also provides the application of the high-temperature transmission mesh belt anti-rust paint in high-temperature pipelines and pipelines in the petroleum, natural gas and chemical industries.
[0022] (3) Beneficial technical effects
[0023] 1. Invented the mechanism of action of an environmentally friendly nitrate ionic liquid. Regarding environmental protection, the system uses L-proline and nitrate anions to create a non-toxic, environmentally friendly system, reducing the use of harmful rust-preventing substances, lowering the ecological burden, and promoting sustainable development. Regarding high-temperature rust prevention, the system accelerates nitrate adsorption and metal surface coverage, delaying corrosion and forming a stable iron ion complex. This enhances adsorption stability and frequency, and increases adsorption efficiency and the hydrophobicity of the metal surface with increasing temperature, thereby mitigating high-temperature corrosion.
[0024] 2. The chitosan polymer of the present invention, first of all, with its natural bio-based components (lauric acid and chitosan) as the core, the chitosan polymer not only realizes the green replacement of traditional harmful chemicals, reduces environmental pollution and dependence on fossil resources, but also promotes resource recycling and ecological balance through its excellent biodegradability. Its anti-corrosion mechanism is mainly reflected in thermal stability: it has good thermal stability and can maintain its anti-corrosion performance under high temperature environment. Enhanced adsorption capacity: through strong adsorption, it can form a dense and stable inhibitory adsorption layer on the metal surface, isolating the metal from direct contact with the corrosive medium. High-efficiency electron donation inhibitor: As an efficient electron donation inhibitor, it can form a strong chemical bond with the metal surface, improve the heat resistance of the inhibitory adsorption layer, and effectively resist thermal stress shock under high temperature environment.
[0025] 3. The sunflower oil-based blend of the present invention is based on environmentally friendly, renewable sunflower seed oil. Its anti-corrosion mechanism is primarily embodied in a tight chemical adsorption mechanism: through tight chemical adsorption to the metal surface, the sunflower oil-based blend maintains stable anti-corrosion performance under high-temperature conditions. It also improves the density and erosion resistance of the anti-rust layer: Through physical and chemical interactions, the density and erosion resistance of the anti-rust layer are significantly improved, providing reliable anti-corrosion protection for metals in extreme environments.
[0026] 4. The carefully selected ingredients in the formula, such as sorbitol, triethanolamine, and sodium carbonate, work synergistically to further optimize the performance stability and efficiency of the anti-rust paint, providing strong support for the entire anti-corrosion system. In summary, the three products of this invention, through their unique environmental protection and anti-corrosion mechanisms, and their close synergy, jointly provide a comprehensive, efficient, and sustainable solution for the anti-corrosion protection of metal materials.
[0027] In summary, the anti-corrosion mechanisms of the above components cover multiple aspects, including environmental protection, high-temperature rust prevention, thermal stability, adsorption capacity, tight chemical adsorption, density and erosion resistance, antioxidant properties, anodic protection, and the synergistic effect of ingredients. These mechanisms together provide a comprehensive, efficient, and sustainable solution for the corrosion protection of high-temperature transmission networks. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is the Fourier transform infrared spectrum FTIR spectrum of the environmentally friendly nitrate ionic liquid prepared in Example 1 of the present invention.
[0029] Figure 2 This is the Fourier transform infrared spectrum FTIR spectrum of the chitosan polymer prepared in Example 1 of the present invention.
[0030] Figure 3 This is a comparison chart of the volume of hydrogen produced by Q235 steel coated with anti-rust paint and without anti-rust paint prepared in Example 1 of the present invention.
[0031] Figure 4 This is a comparison chart of the corrosion inhibition efficiency (η) of Q235 steel coated with anti-rust paint and without anti-rust paint at different temperatures prepared in Example 1 of the present invention.
[0032] Figure 5 This is a comparison chart of the volume of hydrogen generated by Q235 steel coated with anti-rust paint at different temperatures prepared in Example 1 of the present invention and the comparative example. DETAILED DESCRIPTION
[0033] To make the purpose, technical solutions and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.
[0034] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0035] Table 1 Reagents required for Examples and Comparative Examples and corresponding purchasing companies
[0036] Reagents company sorbitol Himaclin Biochemical Technology Co., Ltd. triethanol Shandong West Asia Chemical Co., Ltd. sodium carbonate Jinan Jinhao Chemical Co., Ltd. L-Proline Shandong West Asia Chemical Co., Ltd. Nitric acid Guangzhou Haoyu International Trade Co., Ltd. Lauric acid Guangdong Wengjiang Chemical Reagent Co., Ltd. Methanol Suzhou Qihang Biotechnology Co., Ltd. N,N'-Dicyclohexylcarbodiimide Shandong West Asia Chemical Co., Ltd. Nitrogen Shanghai Minxing Gas Supply Co., Ltd. acetone Shandong Mantanghong New Materials Co., Ltd. sunflower oil Jiangsu Golden Sun Oil Co., Ltd. Formic acid Shanghai MacLean Biochemical Technology Co., Ltd. hydrogen peroxide Shandong West Asia Chemical Co., Ltd. dichloromethane Shandong Mantanghong New Materials Co., Ltd. Sodium bicarbonate Guangdong Wengjiang Chemical Reagent Co., Ltd. polyethylene glycol 400 Shanghai MacLean Biochemical Technology Co., Ltd. Argon Shanghai Minxing Gas Supply Co., Ltd. p-Toluenesulfonic acid Shanghai Ruiyan Petrochemical Co., Ltd. Chitosan Suzhou Qihang Biotechnology Co., Ltd. Ether China National Pharmaceutical Group Corporation
[0037] Example 1
[0038] High-temperature transmission mesh belt anti-rust paint is made from the following components in parts by weight: 10 parts of environmentally friendly nitrate ion liquid, 8 parts of chitosan polymer, 12 parts of sunflower oil-based mixed liquid, 2 parts of sorbitol, 15 parts of triethanolamine, and 4 parts of sodium carbonate;
[0039] The environmentally friendly nitrate ionic liquid is prepared by adding 10 parts by weight of L-proline and 25 ml of deionized water to a flask, followed by adding 2.5 parts of 3 mol / L nitric acid, heating the mixture to 50°C, stirring and keeping the temperature for 20 hours, and finally vacuum drying the mixture at 50°C for 30 minutes to obtain the environmentally friendly nitrate ionic liquid.
[0040] The preparation method of the above-mentioned chitosan polymer is as follows: in parts by weight, 2 parts of chitosan salt, 1 part of lauric acid, 90 ml of deionized water and 80 ml of methanol are mixed evenly, and then 1.5 parts of N,N'-dicyclohexylcarboximide are added, and stirred for 20 hours under a nitrogen atmosphere, and then 300 parts of acetone are added for precipitation and then filtered. Then, the filtered product is washed three times with methanol, and each washing requires that the filtered product is completely submerged with methanol. Finally, the washed filtered product is vacuum dried at room temperature.
[0041] The sunflower oil-based mixed liquid is prepared as follows: 200 parts by weight of sunflower oil and 30 parts of formic acid are added to a reaction vessel, the temperature is then raised to 50° C., 100 parts of hydrogen peroxide is added, and the reaction is continued for 3 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and dissolved in 300 parts of dichloromethane. 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are then added, the mixture is stirred evenly, and the mixture is filtered. The filtrate is then dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil. Finally, 100 parts of epoxy sunflower oil are mixed with 50 parts of polyethylene glycol 400, and the mixture is heated to 60° C. and kept warm for 3 hours to perform a ring-opening reaction, thereby synthesizing the sunflower oil-based mixed liquid.
[0042] The preparation method of the above-mentioned chitosan salt is as follows: in an argon atmosphere, 3 parts of p-toluenesulfonic acid, 2 parts of chitosan and 85 parts of deionized water are mixed evenly by weight, and then heated and stirred at 60°C for 20 hours. After the reaction is completed, the reaction product is washed three times with ether at room temperature, and each washing requires that the reaction product be completely submerged with ether, and then dried completely in a vacuum drying oven at 34°C.
[0043] The present invention also provides a method for preparing a high-temperature transmission mesh belt anti-rust paint, which comprises the following steps:
[0044] Firstly, environmentally friendly nitrate ionic liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol were added to a three-necked flask reactor, slowly heated to 50 °C under magnetic stirring, and then continued to stir for 2 h. During the stirring process, sodium carbonate was used to adjust the pH to 7.0, and then the high-temperature transmission mesh belt anti-rust paint was obtained after cooling.
[0045] Example 2
[0046] High-temperature transmission mesh belt anti-rust paint is made from the following components in parts by weight: 15 parts of environmentally friendly nitrate ion liquid, 12 parts of chitosan polymer, 16 parts of sunflower oil-based mixed liquid, 3 parts of sorbitol, 18 parts of triethanolamine, and 5 parts of sodium carbonate;
[0047] The environmentally friendly nitrate ionic liquid is prepared by adding 12 parts by weight of L-proline and 25 ml of deionized water to a flask, followed by adding 3 parts of 3 mol / L nitric acid, heating the mixture to 58°C, stirring and keeping the temperature for 25 hours, and finally vacuum drying the mixture at 52°C for 45 minutes to obtain the environmentally friendly nitrate ionic liquid.
[0048] The preparation method of the above-mentioned chitosan polymer is as follows: in parts by weight, 3 parts of chitosan salt, 1.5 parts of lauric acid, 92 ml of deionized water and 82 ml of methanol are mixed evenly, and then 2 parts of N, N'-dicyclohexylcarboximide are added, and stirred under a nitrogen atmosphere for 24 hours, and then 300 parts of acetone are added for precipitation and then filtered. Then, the filtered product is washed three times with methanol, and each washing requires that the filtered product is completely submerged with methanol. Finally, the washed filtered product is vacuum dried at room temperature.
[0049] The sunflower oil-based mixed liquid is prepared as follows: 210 parts by weight of sunflower oil and 35 parts of formic acid are added to a reaction vessel, the temperature is then raised to 52° C., 110 parts of hydrogen peroxide is added, and the reaction is continued for 4 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and dissolved in 300 parts of dichloromethane. 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are then added, the mixture is stirred evenly, and the mixture is filtered. The filtrate is then dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil. Finally, 110 parts of epoxy sunflower oil are mixed with 60 parts of polyethylene glycol 400, and the mixture is heated to 70° C. and kept warm for 3 hours for a ring-opening reaction to synthesize the sunflower oil-based mixed liquid.
[0050] The preparation method of the above-mentioned chitosan salt is as follows: in an argon atmosphere, 4 parts of p-toluenesulfonic acid, 3 parts of chitosan and 85 parts of deionized water are mixed evenly by weight, and then heated and stirred at 65°C for 23 hours. After the reaction is completed, the reaction product is washed three times with ether at room temperature, and each washing requires that the reaction product be completely submerged with ether, and then dried completely in a vacuum drying oven at 35°C.
[0051] The present invention also provides a method for preparing a high-temperature transmission mesh belt anti-rust paint, which comprises the following steps:
[0052] Firstly, environmentally friendly nitrate ionic liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol were added to a three-necked flask reactor, slowly heated to 60 °C under magnetic stirring, and then continued to stir for 3 h. During the stirring process, sodium carbonate was used to adjust the pH to 8.0, and then the high-temperature transmission mesh belt anti-rust paint was obtained after cooling.
[0053] Example 3
[0054] High-temperature transmission mesh belt anti-rust paint is made from the following components in parts by weight: 15 parts of environmentally friendly nitrate ion liquid, 12 parts of chitosan polymer, 20 parts of sunflower oil-based mixed liquid, 5 parts of sorbitol, 25 parts of triethanolamine, and 8 parts of sodium carbonate;
[0055] The environmentally friendly nitrate ionic liquid is prepared by adding 18 parts by weight of L-proline and 25 ml of deionized water to a flask, followed by adding 4.5 parts of 3 mol / L nitric acid, heating the mixture to 60°C, stirring and keeping the temperature for 35 hours, and finally vacuum drying the mixture at 55°C for 50 minutes to obtain the environmentally friendly nitrate ionic liquid.
[0056] The preparation method of the above-mentioned chitosan polymer is as follows: in parts by weight, 5 parts of chitosan salt, 2.5 parts of lauric acid, 95 ml of deionized water and 85 ml of methanol are mixed evenly, and then 3 parts of N,N'-dicyclohexylcarboximide are added. The mixture is stirred for 30 hours under a nitrogen atmosphere, and then 300 parts of acetone are added for precipitation and then filtered. The filtered product is then washed three times with methanol, and each washing requires that the filtered product be completely submerged with methanol. Finally, the washed filtered product is vacuum dried at room temperature.
[0057] The sunflower oil-based mixed liquid is prepared as follows: 240 parts by weight of sunflower oil and 40 parts of formic acid are added to a reaction vessel, the temperature is then raised to 55° C., 130 parts of hydrogen peroxide is added, and the reaction is continued for 5 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and dissolved in 300 parts of dichloromethane. 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are then added, the mixture is stirred evenly, and the mixture is filtered. The filtrate is then dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil. Finally, 130 parts of epoxy sunflower oil are mixed with 80 parts of polyethylene glycol 400, and the mixture is heated to 70° C. and kept warm for 3 hours to perform a ring-opening reaction, thereby synthesizing the sunflower oil-based mixed liquid.
[0058] The preparation method of the above-mentioned chitosan salt is as follows: in an argon atmosphere, 6 parts of p-toluenesulfonic acid, 5 parts of chitosan and 85 parts of deionized water are mixed evenly by weight, and then heated and stirred at 70°C for 25 hours. After the reaction is completed, the reaction product is washed three times with ether at room temperature, and each washing requires that the reaction product be completely submerged with ether, and then dried completely in a vacuum drying oven at 40°C.
[0059] The present invention also provides a method for preparing a high-temperature transmission mesh belt anti-rust paint, which comprises the following steps:
[0060] Firstly, environmentally friendly nitrate ionic liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol were added to a three-necked flask reactor, slowly heated to 70 °C under magnetic stirring, and then continued to stir for 3 h. During the stirring process, sodium carbonate was used to adjust the pH to 8, and then the high-temperature transmission mesh belt anti-rust paint was obtained after cooling.
[0061] Example 4
[0062] High-temperature transmission mesh belt anti-rust paint is made from the following components in parts by weight: 25 parts of environmentally friendly nitrate ion liquid, 24 parts of chitosan polymer, 24 parts of sunflower oil-based mixed liquid, 6 parts of sorbitol, 30 parts of triethanolamine, and 9 parts of sodium carbonate;
[0063] The environmentally friendly nitrate ionic liquid is prepared by adding 20 parts by weight of L-proline and 25 ml of deionized water to a flask, followed by adding 5 parts of 3 mol / L nitric acid, heating the mixture to 70°C, stirring and keeping the temperature for 40 hours, and finally vacuum drying the mixture at 60°C for 60 minutes to obtain the environmentally friendly nitrate ionic liquid.
[0064] The preparation method of the above-mentioned chitosan polymer is as follows: in parts by weight, 6 parts of chitosan salt, 3 parts of lauric acid, 100 ml of deionized water and 90 ml of methanol are mixed evenly, and then 3.5 parts of N,N'-dicyclohexylcarboximide are added, and stirred for 35 hours under a nitrogen atmosphere. Then, 300 parts of acetone are added for precipitation and then filtered. Then, the filtered product is washed three times with methanol, and each washing requires that the filtered product be completely submerged with methanol. Finally, the washed filtered product is vacuum dried at room temperature.
[0065] The sunflower oil-based mixed liquid is prepared as follows: 250 parts by weight of sunflower oil and 45 parts of formic acid are added to a reaction vessel, the temperature is then raised to 60° C., 140 parts of hydrogen peroxide is added, and the reaction is continued for 6 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and dissolved in 300 parts of dichloromethane. 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are then added, the mixture is stirred evenly, and the mixture is filtered. The filtrate is then dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil. Finally, 140 parts of epoxy sunflower oil are mixed with 90 parts of polyethylene glycol 400, and the mixture is heated to 80° C. and kept warm for 3 hours to perform a ring-opening reaction, thereby synthesizing the sunflower oil-based mixed liquid.
[0066] The preparation method of the above-mentioned chitosan salt is as follows: in an argon atmosphere, 7 parts of p-toluenesulfonic acid, 6 parts of chitosan and 85 parts of deionized water are mixed evenly by weight, and then heated and stirred at 80°C for 30 hours. After the reaction is completed, the reaction product is washed three times with ether at room temperature, and each washing requires that the reaction product be completely submerged with ether, and then dried completely in a vacuum drying oven at 45°C.
[0067] The present invention also provides a method for preparing a high-temperature transmission mesh belt anti-rust paint, which comprises the following steps:
[0068] Firstly, environmentally friendly nitrate ionic liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol were added to a three-necked flask reactor, slowly heated to 80 °C under magnetic stirring, and then continued to stir for 4 h. During the stirring process, sodium carbonate was used to adjust the pH to 9.0, and then the high-temperature transmission mesh belt anti-rust paint was obtained after cooling.
[0069] Example 5
[0070] The method is basically the same as Example 1, except that the amount of chitosan polymer in the anti-rust paint is 24 parts.
[0071] Comparative Example 1
[0072] The method is basically the same as Example 1, except that the environmentally friendly nitrate ion liquid is not added to the anti-rust paint.
[0073] Comparative Example 2
[0074] The method is basically the same as Example 1, except that the chitosan polymer is not added to the anti-rust paint.
[0075] Comparative Example 3
[0076] The method is basically the same as Example 1, except that the sunflower oil-based mixed liquid is not added to the anti-rust paint.
[0077] Characterization Tests:
[0078] The embodiment 1 of the present invention uses Fourier transform infrared spectroscopy (FTIR) technology, and the infrared spectrum test range is 4000cm -1 ~400cm -1 , the instrument model is Nicolet iS50, which systematically verified that the chemical structures of the three key materials prepared were consistent with expectations, thus strongly demonstrating their effectiveness individually and in synergy. Figure 1 The FTIR spectrum of environmentally friendly nitrate ion liquid is at a specific wavelength (1590cm -1 、1380cm -1 、1723cm -1 etc.) clearly demonstrated the presence of functional groups such as C=N, CN, and C=O, directly proving the non-toxic and environmentally friendly properties of the ionic liquid and the accuracy of its chemical composition. Figure 2 It further revealed that chitosan polymer -1 This is not only a clear sign of C=O amide, but also directly proves that an amide bond has been successfully formed between the CS amino group and the lauric acid carboxyl group. In addition, the NH stretching band and other characteristic peaks (such as 1625cm -1 、937cm -1 、1217cm-1 、1301cm -1 ) confirmed, together building the stable chemical structure foundation of the polymer. In summary, the FTIR analysis results provide strong evidence for the effectiveness of the environmentally friendly nitrate ionic liquid and chitosan polymer in the present invention, demonstrating their excellent application prospects in the fields of environmental protection and corrosion prevention.
[0079] Performance testing:
[0080] Amount of hydrogen released: In order to accurately evaluate the release rate of hydrogen, this study adopted the classic water position replacement method, which is similar in principle to previous studies, but has been optimized in implementation details. Specifically, the experiment first accurately measured 100 ml of 1M hydrochloric acid solution as the corrosion medium and placed it in a well-sealed container. Subsequently, a Q235 steel specimen with a size of 3.5 cm × 2.5 cm was carefully cleaned and dried, and then completely immersed in the test solution to ensure that the surface of the specimen was in full contact with the solution and no bubbles were attached. This study shows the change in the volume of hydrogen produced by the corrosion of Q235 steel in 1 mol / L HCl solution over time at different temperatures, without and with anti-rust paint. The results show that with the extension of the immersion time of the steel, the amount of hydrogen generated shows a clear and significant increasing trend. Based on the volume of hydrogen produced, the hydrogen generation rate (Hr) was evaluated using the following formula: Hr = (V2-V1) / (t2-t1), where V2 and V1 represent the volumes of hydrogen released measured at time points t2 and t1, respectively.
[0081] Electrochemical tests were performed on a CHI760E workstation (Shanghai Chenhua) using a standard three-electrode system in a 150 mL beaker. Each experiment involved 100 mL of solution to ensure reproducible results. Q235 steel was used as the working electrode, pre-polished with 400 to 2000 grit sandpaper. A platinum sheet (2 × 2 cm², Tianjin Aida) served as the counter electrode, and a saturated calomel electrode (same as Tianjin Aida) served as the reference electrode. During the test, a Lujin capillary from Chongqing Chuandong Chemical was used, with its tip close to the working electrode to minimize the influence of solution resistance. Before the experiment, the Q235 steel electrode was immersed in the corrosive solution for 1800 seconds for open circuit potential (OCP) stabilization. Subsequently, electrochemical impedance spectroscopy (EIS) tests were performed based on the OCP stabilization value, with a frequency range of 100 kHz to 10 MHz and an excitation voltage of 0.005 V. Next, the polarization curve test was performed with the scan range set to OCP ± 0.25 V and the scan rate set to 1 mV / s. The entire electrochemical test process was repeated three times under uniform conditions to ensure high reproducibility of the data. In addition, the corrosion current density i was obtained using the Tafel extrapolation method. coor , where corrosion inhibition efficiency (η) = (i coor -i0) / icoor , where i0 is the corrosion current density without anti-rust paint.
[0082] Figure 3 This is a volume comparison diagram of hydrogen produced by Q235 steel coated with anti-rust paint and not coated with anti-rust paint prepared in Example 1 of the present invention. The figure shows the comparative study results of hydrogen production rate under specific conditions for Q235 steel samples coated with and not coated with anti-rust paint in Example 1 of the present invention. Specifically, for Q235 steel samples coated with anti-rust paint, as the experimental temperature gradually increases and the exposure time is extended, the hydrogen release rate shows a slowly increasing trend. This phenomenon indicates that anti-rust paint plays a significant role in inhibiting corrosion reactions and slowing down hydrogen precipitation. In contrast, under high temperature conditions of 90 degrees Celsius, the amount of hydrogen produced by Q235 steel samples not coated with anti-rust paint increases sharply as the experimental time goes by. This significant difference not only intuitively reflects the acceleration of the corrosion process, but also strongly proves the effectiveness of anti-rust paint in inhibiting corrosion and protecting the metal substrate. Therefore, Figure 3 The data presented not only verify the positive contribution of anti-rust paint to the corrosion resistance of Q235 steel, but also provide a strong experimental basis for the optimization and application of subsequent anti-rust technology.
[0083] Figure 4 This is a comparison chart of the corrosion inhibition efficiency (η) of Q235 steel coated with anti-rust paint and without anti-rust paint at different temperatures prepared in Example 1 of the present invention. Figure 4 The comparative situation of the corrosion inhibition efficiency (η) of Q235 steel coated with anti-rust paint and not coated with anti-rust paint under different temperature conditions prepared in Example 1 of the present invention is described in detail. For the Q235 steel sample coated with anti-rust paint, as the ambient temperature gradually increases, its corrosion inhibition efficiency (η) slightly decreases from the initial 93% to 88%, but it still maintains a high level of corrosion inhibition performance as a whole. More importantly, in the high temperature section, the corrosion inhibition efficiency of the anti-rust paint gradually stabilizes and does not show a significant decline. This phenomenon fully proves that the anti-rust paint can still exert an excellent anti-corrosion effect in a high temperature environment and effectively slows down the corrosion rate of the steel. In contrast, the corrosion inhibition efficiency (η) of the Q235 steel sample not coated with anti-rust paint at different temperatures shows a more obvious downward trend, significantly decreasing from the initial 85% to 65%. This significant change not only reflects the high sensitivity of unprotected steel to temperature changes, but also further highlights the important role of anti-rust paint in improving the corrosion resistance of metal materials and extending their service life. Therefore, Figure 4 The data presented not only provide strong evidence for the performance evaluation of anti-rust paint, but also provide valuable reference information for the application of anti-rust technology in different temperature environments.
[0084] Figure 5The following chart compares the volume of hydrogen generated at different temperatures for Q235 steel coated with anti-rust paint, prepared in Example 1 of the present invention and in the comparative example. An in-depth analysis of the trends in the volume of hydrogen generated by the anti-rust paint-coated Q235 steel samples prepared in Example 1 of the present invention and in the comparative example at different temperature gradients was performed. The results demonstrate that Example 1 exhibits excellent corrosion resistance, demonstrated by its ability to significantly inhibit hydrogen evolution in high-temperature environments.
[0085] The properties of the anti-rust paints of Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in Table 2.
[0086] Table 2 Performance of antirust paints of Examples 1 to 5 and Comparative Examples 1 to 3
[0087]
[0088] The main difference between Comparative Example 1 and Example 1 is whether the coating contains an environmentally friendly nitrate ionic liquid. It can be seen from Table 2 that the inclusion of an environmentally friendly nitrate ionic liquid can significantly improve the anti-corrosion performance of the anti-rust paint. This is because the environmentally friendly nitrate ionic liquid accelerates molecular adsorption at high temperatures, enhances chemical adsorption to form iron ion complexes, increases the contact frequency of the electrode surface, promotes the desorption of water molecules and enhances surface hydrophobicity, thereby significantly delaying and inhibiting metal corrosion in a high temperature environment.
[0089] The main difference between Comparative Example 2 and Example 1 is whether the coating contains chitosan polymer. It can be seen from Table 2 that the addition of chitosan polymer can significantly improve the anti-corrosion performance of the anti-rust paint. This is because the chitosan polymer has excellent high-temperature corrosion resistance due to its thermal stability, strong adsorption to form a dense protective layer, and as an efficient electron donor, it strongly bonds with the metal to resist high-temperature corrosion.
[0090] The main difference between Comparative Example 3 and Example 1 is whether the coating contains a sunflower oil-based mixed liquid. It can be seen from Table 2 that the inclusion of a sunflower oil-based mixed liquid can significantly improve the anti-corrosion performance of the anti-rust paint. This is because the sunflower oil-based mixed liquid forms a stable chemical adsorption layer at high temperature, and the functional groups strongly bond to the metal surface, isolating the corrosive medium, maintaining structural integrity, enhancing adhesion and erosion resistance, and effectively protecting the metal from corrosion.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that any equivalent structural changes made based on the contents of the present invention's description and drawings under the concept of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. High temperature transmission mesh belt anti-rust paint, characterized in that: The invention is prepared from the following components in parts by weight: 10 to 25 parts of environmentally friendly nitrate ion liquid, 8 to 24 parts of chitosan polymer, 12 to 24 parts of sunflower oil-based mixed liquid, 2 to 6 parts of sorbitol, 15 to 30 parts of triethanol and 4 to 9 parts of sodium carbonate.
2. The high temperature transmission mesh belt anti-rust paint according to claim 1, characterized in that: The preparation method of the environmentally friendly nitrate ion liquid is as follows: by weight, 10 to 20 parts of L-proline and 25 ml of deionized water are added into a flask, then 2.5 to 5 parts of 3 mol / L nitric acid are added, then the temperature is raised to 50 to 70° C., stirred and kept warm for 20 to 40 hours, and finally vacuum dried at 50 to 60° C. for 30 to 60 minutes to obtain the environmentally friendly nitrate ion liquid.
3. The high temperature transmission mesh belt anti-rust paint according to claim 1, characterized in that: The preparation method of the chitosan polymer is as follows: by weight, 2 to 6 parts of chitosan salt, 1 to 3 parts of lauric acid, 90 to 100 ml of deionized water and 80 to 90 ml of methanol are mixed evenly, then 1.5 to 3.5 parts of N, N'-dicyclohexylcarbocyanine are added, and stirred for 20 to 35 hours under a nitrogen atmosphere, and then 300 parts of acetone are added for precipitation and then filtered, and then the filtered product is washed three times with methanol, and each washing needs to completely submerge the filtered product with methanol, and finally the washed filtered product is vacuum dried at room temperature.
4. The high temperature transmission mesh belt anti-rust paint according to claim 1, characterized in that: The preparation method of the sunflower oil-based mixed liquid is as follows: by weight, 200 to 250 parts of sunflower oil and 30 to 45 parts of formic acid are added to a reaction container, then the temperature is raised to 50 to 60° C., 100 to 140 parts of hydrogen peroxide are added to continue the reaction for 3 to 6 hours, after the reaction is completed, the reaction mixture is cooled to room temperature, dissolved in 300 parts of dichloromethane, then 100 parts of a mixed solution of deionized water and sodium bicarbonate in a mass ratio of 1:1 are added, stirred evenly and filtered, and then the filtrate is dried in a vacuum drying oven at room temperature to obtain epoxy sunflower oil, and finally 100 to 140 parts of epoxy sunflower oil and 50 to 90 parts of polyethylene glycol 400 are mixed, heated to 60 to 80° C. and kept warm for 3 hours to perform a ring-opening reaction to synthesize the sunflower oil-based mixed liquid.
5. The high temperature transmission mesh belt anti-rust paint according to claim 2, characterized in that: The mass ratio of the L-proline to 3 mol / L nitric acid is 4:
1.
6. The high temperature transmission mesh belt anti-rust paint according to claim 3, characterized in that: The preparation method of the chitosan salt is as follows: by weight, 3 to 7 parts of p-toluenesulfonic acid, 2 to 6 parts of chitosan and 85 parts of deionized water are mixed evenly in an argon atmosphere, and then heated and stirred at 60 to 80° C. for 20 to 30 hours. After the reaction is completed, the mixture is washed three times with ether at room temperature, and each washing requires that the reaction product is completely submerged with ether, and then completely dried in a vacuum drying oven at 34 to 45° C.
7. The high temperature transmission mesh belt anti-rust paint according to claim 6, characterized in that: The mass ratio of the chitosan salt to the lauric acid is 2:
1.
8. The method for preparing the anti-rust paint for high-temperature transmission mesh belt according to any one of claims 1 to 7, characterized in that: It consists of the following steps: Firstly, environmentally friendly nitrate ion liquid, chitosan polymer, sunflower oil-based mixed liquid, sorbitol and triethanol are added into a three-necked flask reactor, heated to 50-80°C under magnetic stirring, and then stirred for 2-4 hours. During the stirring process, the pH value is adjusted to 7.0-9.0 with sodium carbonate, and then the high-temperature transmission mesh belt anti-rust paint is obtained after cooling.
9. Application of the high-temperature transmission mesh belt anti-rust paint prepared by the preparation method according to claim 8 in high-temperature pipelines and pipelines in the petroleum, natural gas and chemical industries.
Citation Information
Patent Citations
Waterborne rust-proof paint and preparation method thereof
CN109135523A